Investigation of thermal properties of carbon nanotubes and carboxyl group - functionalized carbon nanotubes - Abaszade, R.G.; Aliyev, E.M.; Babanli, M.B.; Kotsyubynsky, V.O.; Zapukhlyak, R.I.; Mammadov, A.G.; Budak, H.F.; Kasapoglu, A.E.; Gür, E.; Margitych, T.O.; et al. (Physics and Chemistry of Solid State, 2023)
Thermal properties characterizations for carbon nanotubes (CNTs), carboxyl group-functionalized carbon nanotubes (FCNT), and graphite were presented in the paper. TGA/DSC and TEM techniques were used for characterization. The features of TGA characteristics transformation for synthesized carbon nanomaterials were investigated. The specific heat capacities of the samples at a constant pressure increased as the temperature increased.